Perancangan Aplikasi Penyandian Pesan Teks Menggunakan Vigenere Chiper Dan Algoritma Elgamal - -, Basyiah; Syahputra, Fahmy (MEANS (Media Informasi Analisa dan Sistem), 2018)
The development of technology and information, especially in the field of information communication, is very rapidly developing, one of them is the communication media of smart phones. one of the facilities provided by smart phones is the exchange of information in the form of sending text messages through Short Message Service (SMS). This information can be in the form of important data that not all parties can find out. Some risks that can threaten message security in SMS services include SMS Spoofing, Snooping SMS and SMS Interception. The message security system in the form of text is one of them with a cryptographic system. Cryptography is a message security science that aims to maintain the confidentiality of information contained in data so that information cannot be known by irresponsible parties. Cryptography changes the meaningful writing to be meaningless by using various kinds of cryptographic algorithms. The algorithms used are ElGamal and Vigenere Chiper. The ElGamal algorithm uses 2 different keys in encrypting and decrypting the public key for encryption and the private key for decryption. While Vigenere chipers only use one key that is the same for encryption and description. With the text message encoding application using the ElGamal and Vigenere Chiper algorithms, it is expected to help smart phone users with the operating system.